In-situ preparation method of modified graphene quantum dot / ZnO gas-sensitive material
By preparing modified graphene quantum dots/ZnO gas-sensitive materials in situ on Al2O3 gas-sensitive ceramic tubes, the existing ZnO gas-sensitive materials have been solved, and the problems of low sensitivity, poor selectivity and high operating temperature when detecting harmful chemicals and volatile organic compounds are achieved, and lower operating temperatures and higher sensitivity and selectivity are achieved.
Patent Information
- Application Number
- CN202411883729.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-12-19
AI Technical Summary
Existing ZnO gas-sensitive materials have problems such as low sensitivity, poor selectivity and high operating temperature when detecting harmful chemicals and volatile organic compounds, which hinder their practical application.
The modified graphene quantum dot/ZnO gas-sensitive material was prepared in situ on Al2O3 gas-sensitive ceramic tube by seed induction method. The gas-sensitive performance was improved through hydrothermal method and solvothermal reaction steps, combined with ammonia water modification.
It reduces the optimal working temperature of the gas-sensitive element, improves the sensitivity and selectivity to ethanol gas, and is simple in process, environmentally friendly and low-cost.
Smart Images

Figure CN119684036A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of semiconductor gas-sensitive material preparation, and particularly relates to an in-situ preparation method of a modified graphene quantum dot / ZnO gas-sensitive material. Background Art
[0002] With the accelerated development of modern industrial technology, more and more toxic and harmful gases are continuously emitted, which will pose a threat to people's living environment. Therefore, the detection of these gas molecules is particularly necessary in many fields, especially in the field of environmental monitoring. Metal oxide sensors are one of the preferred candidate devices for detecting low-concentration volatile organic compounds. They have the advantages of simple measurement, durability, easy to manufacture into small size and low cost. In the research of gas-sensitive materials of metal oxide sensors, the research on nano ZnO has attracted much attention. ZnO is a semiconductor material with a wide direct band gap (3.37eV). Due to its good response to various reducing and oxidizing gases, low price, good chemical and physical stability under sensor working conditions, and environmental friendliness, it has received widespread attention in gas sensing applications. However, ZnO as a gas-sensitive material still faces some challenges. There are problems such as low sensitivity, poor selectivity, and high operating temperature in the detection of harmful chemicals and volatile organic compounds, which hinders its practical application.
[0003] Graphene quantum dots (GQDs) have small lateral dimensions and relatively high electron mobility. Due to the defects in their structure and functional groups, they can provide many active sites to promote the adsorption of gas molecules. Therefore, modifying ZnO with GQDs can improve its gas sensing performance. In addition, in order to further change the charge transfer between GQDs and metal oxides and provide more active sites, people have used different methods to modify GQDs in order to improve the performance of gas sensors. Current research shows that in SnO 2 The nitrogen-doped GQDs can effectively increase their NO 2 The existing technology successfully prepared the N-GQDs modified ZnO gas-sensitive material by hydrothermal method, and prepared the gas-sensitive element by traditional thick film preparation process. It was found that the working temperature of the element was greatly reduced, and the NO 2 At present, there is little research on modified GQDs / ZnO gas-sensitive materials, especially the use of seed induction method to directly deposit on Al 2 O 3 There is no report on the preparation of corresponding gas-sensitive materials on gas-sensitive ceramic tubes.
[0004] At present, thick film gas sensors are still often produced by traditional manual coating methods, which is time-consuming and cumbersome, and the uniformity of the resulting gas sensors is poor. Therefore, the present invention explores a simple, environmentally friendly and low-cost seed induction method to directly deposit the Al 2 O 3 Gas-sensitive materials are prepared on gas-sensitive ceramic tubes. Summary of the invention
[0005] The object of the present invention is to provide a 2 O 3 A method for in-situ preparation of modified graphene quantum dots / ZnO gas-sensitive materials on gas-sensitive ceramic tubes. The present invention uses a seed induction method to prepare a modified graphene quantum dot / ZnO gas-sensitive material on a gas-sensitive ceramic tube. 2 O 3 The gas-sensitive ceramic tube is used as the substrate, and graphene quantum dots, zinc chloride and sodium carbonate are used as the main raw materials by a simple hydrothermal method. 2 O 3 Graphene quantum dots / ZnO gas-sensitive materials are prepared in situ on gas-sensitive ceramic tubes. Furthermore, the graphene quantum dots / ZnO gas-sensitive materials are modified by ammonia water, which has the advantages of simple operation, green environmental protection and low price. It can be used to detect ethanol gas to improve the performance of ZnO gas-sensitive elements in detecting ethanol. The present invention discloses an in-situ preparation method of modified graphene quantum dots / ZnO gas-sensitive materials, comprising the following steps:
[0006] (1)Al 2 O 3 Gas sensitive ceramic tube pretreatment: Al 2 O 3 The gas-sensitive ceramic tube is soaked in NaOH solution to remove organic pollutants on its surface, and hydroxyl groups can also be introduced on its surface to activate the ceramic tube. Subsequently, the gas-sensitive ceramic tube soaked in alkali solution is ultrasonically cleaned with deionized water, taken out after 45-55 minutes, and placed in a 70-80℃ oven for drying;
[0007] (2) Preparation of ZnO seed crystals and their loading on gas-sensitive ceramic tubes: Weigh zinc acetate dihydrate and place it in a beaker, add anhydrous ethanol, and after the zinc acetate dihydrate is dissolved, add polyvinyl pyrrolidone and ultrasonically disperse for 20-30 minutes. Subsequently, use a disposable pipette to quickly drop 0.5 mol / L NaOH ethanol solution into the above solution, and continue ultrasonically dispersing for 30 minutes to obtain a ZnO seed crystal solution. The mass ratio of hydrated zinc acetate, anhydrous ethanol, polyvinyl pyrrolidone and NaOH ethanol solution is 1:90-100:1-2:200-220; Take the Al2O3 described in step (1) 2 O 3 The gas-sensitive ceramic tube allows the ZnO seed crystal solution to form a uniform film on its surface, and after drying, the ZnO seed crystal can be loaded on the gas-sensitive ceramic tube;
[0008] (3) Preparation of graphene quantum dot solution: a certain amount of citric acid is dissolved in deionized water, stirred for a certain period of time, and heated in an oven at 180-200° C. to melt. The resulting liquid is adjusted to a pH of 7 with a NaOH solution, and the upper clear liquid is taken after centrifugation to obtain a graphene quantum dot solution.
[0009] (4) In-situ preparation of graphene quantum dot / ZnO gas-sensitive material: Sodium dodecyl sulfate and the graphene quantum dot solution prepared in step (3) are added to the zinc chloride aqueous solution respectively, and stirred for 30-40 minutes; then, sodium carbonate solution is quickly added dropwise to the mixed solution under magnetic stirring, and stirring is continued for 1-1.5 hours. The obtained mixed solution and the gas-sensitive ceramic tube loaded with ZnO crystals are placed in the lining of the reactor together for hydrothermal reaction; after the reaction is completed and the reactor is cooled, the gas-sensitive ceramic tube is taken out, washed with deionized water and anhydrous ethanol for multiple times, and placed in a 70-80°C oven for drying; finally, the gas-sensitive ceramic tube is calcined at 300-320°C for 1-2 hours, and the graphene quantum dot / ZnO gas-sensitive material can be prepared in-situ on the gas-sensitive ceramic tube.
[0010] (5) Preparation of modified graphene quantum dot / ZnO gas sensitive material: Measure ammonia water and add it to ethylene glycol solution at a molar ratio of 1:300-350. After stirring evenly, transfer it into the lining of a reactor and put the ceramic tube in step (4) into it. Place the reactor in an oven for solvent thermal reaction. After the reaction is completed, take out the ceramic tube, wash it with ethanol several times, and dry it to obtain the modified graphene quantum dot / ZnO gas sensitive material.
[0011] Preferably, in step (1), the concentration of the NaOH solution is 0.1 mol / L, and the soaking time is 5 to 10 min.
[0012] Preferably, in step (2), the ZnO seed is loaded on the Al 2 O 3 The gas-sensitive ceramic tube is usually sprayed and dried 5 to 8 times, and then placed in an oven at 80°C for drying before use.
[0013] Preferably, in step (3), the amount of citric acid used is 0.5-1.5 g, and the heating and melting time at 180° C. is 2 h.
[0014] Preferably, in step (4), the graphene quantum dot solution is prepared using 0.76 g of citric acid, and the amount used is 1 to 4 mL.
[0015] Preferably, in step (4), the concentration of the zinc chloride aqueous solution is 1.50 mol / L, the concentration of the sodium carbonate solution is 0.80 mol / L, and the molar ratio of the sodium dodecyl sulfate to the zinc chloride is 1:65 to 1:70.
[0016] Preferably, in step (4), the temperature of the hydrothermal reaction is 110 to 170° C., and the time of the hydrothermal reaction is 12 to 24 hours.
[0017] Preferably, in step (5), the amount of ammonia water used is 200 μL, the amount of ethylene glycol solution used is 50 mL, the solvent thermal reaction temperature is 150-180° C., and the reaction time is 2-4 h.
[0018] The present invention also provides a gas-sensitive element, which comprises the modified graphene quantum dot / ZnO gas-sensitive material prepared by the method of the present invention.
[0019] Preferably, compared with pure ZnO gas sensor, the modified graphene quantum dot / ZnO gas sensor has an optimal operating temperature reduced by about 170°C and can be used for the detection of ethanol gas. The gas sensor shows excellent selectivity for ethanol gas in ethanol, acetone, benzene, ammonia and methanol gas atmospheres.
[0020] The advantages and effects of the present invention are:
[0021] The first published method of seed induction in Al 2 O 3 A method for in-situ preparation of modified graphene quantum dots / ZnO gas-sensitive materials on gas-sensitive ceramic tubes; the method of the present invention is to prepare modified graphene quantum dots / ZnO gas-sensitive materials on Al 2 O 3 The modified graphene quantum dot / ZnO gas-sensitive material is prepared in situ on the gas-sensitive ceramic tube, which is simple to operate, environmentally friendly and low in cost. The modified graphene quantum dot / ZnO gas-sensitive element prepared by the present invention has a low optimal operating temperature and exhibits excellent selectivity for ethanol gas. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 These are scanning electron microscope photos of modified graphene quantum dots / ZnO gas-sensitive materials prepared under different conditions in Examples 1 to 4.
[0023] Figure 2 This is the energy spectrum analysis spectrum of the modified graphene quantum dots / ZnO gas sensitive material prepared in Example 2.
[0024] Figure 3 The sensitivity-temperature curves of the gas sensors prepared in Examples 1 to 4 and Comparative Example 1.
[0025] Figure 4This is a test chart of the sensitivity of the gas sensors prepared in Example 2 and Comparative Example 1 to 5 different gases at 100 ppm.
[0026] Figure 5 Response recovery time of the N-2 gas sensor prepared in Example 2.
[0027] Figure 6 The response recovery time of the PZ-150 gas sensor prepared in Comparative Example 1. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below in conjunction with the embodiments and drawings.
[0029] Example 1
[0030] (1)Al 2 O 3 Pretreatment of gas-sensitive ceramic tube: Al 2 O 3 The gas-sensitive ceramic tube was immersed in 0.1 mol / L sodium hydroxide solution for 5 min, ultrasonically cleaned with deionized water, taken out after 45 min, and dried in an oven at 80 °C for later use;
[0031] (2) Preparation of ZnO seed crystals and loading on gas-sensitive ceramic tubes: Weigh 0.176 g of zinc acetate dihydrate and place it in a beaker, add 20 mL of anhydrous ethanol, and after the zinc acetate dihydrate is dissolved, add 0.176 g of polyvinyl pyrrolidone and ultrasonically disperse for 20 min. Subsequently, use a disposable pipette to quickly drop 50 mL of 0.5 mol / L sodium hydroxide ethanol solution into the above solution, and continue ultrasonically dispersing for 30 min to obtain a ZnO seed crystal solution; take the Al pretreated in step (1) 2 O 3 The gas-sensitive ceramic tube is made to form a uniform film of ZnO seed solution on its surface by drop coating method, and the drop coating-drying cycle is repeated 8 times. Finally, the gas-sensitive ceramic tube is placed in an oven at 80°C for drying, and ZnO seed can be loaded on the gas-sensitive ceramic tube.
[0032] (3) Preparation of graphene quantum dot solution: 0.76 g of citric acid was weighed using an electronic balance, dissolved in 20 mL of deionized water, stirred for 10 min, and heated in an oven at 180° C. to melt. The resulting liquid was adjusted to a pH of 7 using a NaOH solution. After centrifugation, the supernatant was collected to obtain the graphene quantum dot solution.
[0033] (4) In-situ preparation of graphene quantum dots / ZnO gas-sensitive materials:
[0034] 3.28 g of zinc chloride was weighed with an electronic balance and dissolved in 60 mL of deionized water to obtain a zinc chloride solution. 0.40 g of sodium dodecyl sulfate and 1.0 mL of the graphene quantum dot solution described in step (3) were added to the zinc chloride solution respectively, and stirred for 30 min with a magnetic stirrer for later use; at the same time, 5.08 g of anhydrous sodium carbonate was weighed and dissolved in 60 mL of deionized water under magnetic stirring to obtain a sodium carbonate solution, and the sodium carbonate solution was continuously added dropwise to the above-mentioned mixed solution with a disposable pipette, and stirring was continued for 1 h.
[0035] The mixed solution and the gas-sensitive ceramic tube loaded with ZnO seed crystals were placed in the inner lining of the reactor, and the reactor was placed in an oven at 150°C for hydrothermal reaction for 12 hours. After the reactor was cooled, the gas-sensitive ceramic tube was taken out, washed with deionized water and anhydrous ethanol for three times respectively, and placed in an oven at 80°C for drying.
[0036] Finally, the gas-sensitive ceramic tube is placed in a muffle furnace and calcined at 300°C for 2 hours to in-situ prepare the graphene quantum dots / ZnO gas-sensitive material on the gas-sensitive ceramic tube.
[0037] (5) Preparation of modified graphene quantum dots / ZnO gas-sensitive materials:
[0038] Measure 200 μL of ammonia water, add it to 50 mL of ethylene glycol solution, stir it evenly, and then transfer it to the lining of the reactor, and put the ceramic tube in step (4) into it; place the reactor in a 150°C oven for solvent thermal reaction, and the reaction time is 4 hours; after the reaction is completed, take out the ceramic tube, wash it with ethanol several times, and dry it to obtain the modified graphene quantum dot / ZnO gas sensitive material, which is marked as N-1. The scanning electron microscope photo of N-1 is as follows Figure 1 (a) Figure 1 (a) It can be seen that the morphology of the modified graphene quantum dots / ZnO gas-sensitive material is a nanosheet structure with irregular shapes and sizes, so that more gaps can be formed between the particles, which is beneficial to improving its gas-sensing performance.
[0039] Embodiments 2 to 4
[0040] The amounts of the graphene quantum dot solution in step (4) of Example 1 were changed to 2.0, 3.0 and 4.0 mL respectively, and the remaining steps were the same as in Example 1.
[0041] The modified graphene quantum dots / ZnO gas-sensitive materials prepared in Examples 2 to 4 are marked as N-2, N-3 and N-4, respectively.
[0042] The SEM photo of the modified graphene quantum dot / ZnO gas sensitive material prepared in Example 2 is as follows: Figure 1As shown in (b), it can be seen that its morphology is still an irregular nanosheet structure, but its size uniformity is significantly improved, and the distribution of the nanosheets in space is three-dimensional, and more gaps are formed between the nanosheets with different orientations, which is undoubtedly beneficial to improving its gas sensing performance; the SEM photos of the modified graphene quantum dots / ZnO gas sensing materials prepared in Example 3 and Example 4 are shown respectively. Figure 1 (c) and Figure 1 As shown in (d), it can be clearly seen that with the increase in the amount of graphene quantum dots added, the size of the nanosheets tends to increase, the contact between the sheets becomes closer, and the distribution orientation of the nanosheets tends to be consistent.
[0043] Comparative Example 1
[0044] In step (4) of Example 1, no graphene quantum dot solution is added, and the modification treatment of step (5) is not performed. The remaining steps are the same as those of Example 1. Pure ZnO gas-sensitive material can be prepared in situ on the gas-sensitive ceramic tube and is labeled as PZ-150.
[0045] Application and testing of gas sensors:
[0046] Use a file to grind the electrode tip of the sensor base to make it rough, and adhere flux to the tips of the four signal electrodes of the base. Take the gas-sensitive ceramic tube described in Examples 1 to 4 and Comparative Example 1, pass a needle through the ceramic tube, place it on the sensor base, and weld a signal electrode of the base to the signal wire of the ceramic tube. Take out the needle, clamp the remaining signal wires with tweezers, and weld them in turn. After the four signal wires are welded, insert the nickel-chromium heating wire into the ceramic tube and weld it; finally, use a multimeter to measure the resistance between the base heating electrodes. First, age the gas-sensitive element on an aging bench at 80mA for 48 hours, and then age it at 160mA for 8 hours.
[0047] The response values of five gas sensors to 100ppm ethanol gas at different temperatures were tested. The results are as follows: Figure 3 As shown. It can be seen that the operating temperature of the modified graphene quantum dot / ZnO gas sensor is significantly lower than that of pure ZnO, among which the optimal operating temperature of the N-2 gas sensor is 170°C lower than that of the pure ZnO (PZ-150) element. At their respective optimal operating temperatures, the sensitivity of the modified graphene quantum dot / ZnO gas sensor to 100ppm ethanol is higher than that of the pure ZnO gas sensor, and the sensitivity of the N-2 element is nearly twice that of the pure ZnO element.
[0048] The response values of N-2 and PZ-150 gas sensors to different gases such as ethanol, acetone, benzene, ammonia and methanol were tested. The concentration of the gas was 100ppm. Each gas sensor was tested at its optimal operating temperature. The results are as follows: Figure 4It is obvious that the N-2 gas sensor has excellent selectivity for ethanol gas.
[0049] The response recovery time of N-2 and PZ-150 gas sensors in 100ppm ethanol atmosphere was tested. The results are as follows: Figure 5 and Figure 6 As shown in the figure, the addition of modified graphene quantum dots shortens the response time of the device from 7s to 5.7s, and greatly shortens the recovery time of the device from 154s to 21.5s.
Claims
1. An in-situ preparation method of modified graphene quantum dots / ZnO gas sensitive materials, characterized in that: The following steps are involved: S1. Soak the Al2O3 gas-sensitive ceramic tube in a NaOH solution, then perform ultrasonic cleaning, take it out after 45-55 minutes, and dry it in a 70-80°C oven for later use; S2, weigh zinc acetate hydrate and put it in a beaker, add anhydrous ethanol, after zinc acetate dihydrate is dissolved, add polyvinyl pyrrolidone, and ultrasonically disperse for 20-30 minutes, add 0.5 mol / L NaOH ethanol solution dropwise into the above solution, and continue ultrasonically dispersing for 30-40 minutes to obtain a ZnO seed solution, wherein the mass ratio of zinc acetate hydrate, anhydrous ethanol, polyvinyl pyrrolidone and NaOH ethanol solution is 1:90-100:1-2:200-220; take the Al2O3 gas-sensitive ceramic tube described in step S1 to uniformly form a film of the ZnO seed solution on its surface, and dry it for later use; S3, citric acid is dissolved in deionized water, and the mixture is heated in an oven at 180-200°C to melt, and the pH of the resulting liquid is adjusted to 7 with a NaOH solution, and the supernatant is collected after centrifugation to obtain a graphene quantum dot solution; S4, respectively adding sodium dodecyl sulfate and the graphene quantum dot solution prepared in step S3 to the zinc chloride aqueous solution, and stirring for 30-40 minutes; then, rapidly dropping the sodium carbonate solution into the mixed solution under magnetic stirring, and continuing stirring for 1-1.5 hours, and placing the obtained mixed solution and the gas-sensitive ceramic tube obtained in step S2 into the inner lining of the reactor together for hydrothermal reaction; after the reaction is completed and the reactor is cooled, taking out the ceramic tube, washing it with deionized water and anhydrous ethanol for several times, and drying it in a 70-80°C oven; finally, calcining the ceramic tube at 300-320°C for 1-2 hours; S5. Add ammonia water to the ethylene glycol solution at a molar ratio of 1:300-350, stir evenly and transfer into the inner lining of the reactor, and put the ceramic tube obtained in step S4 into it; place the reactor in an oven for solvent thermal reaction, and after the reaction is completed, take out the ceramic tube, wash it with ethanol several times, and dry it to obtain the modified graphene quantum dot / ZnO gas sensitive material.
2. The in-situ preparation method of modified graphene quantum dots / ZnO gas sensitive material according to claim 1, characterized in that: The concentration of the NaOH solution in step S1 is 0.1 mol / L, and the soaking time is 5 to 10 minutes.
3. The in-situ preparation method of modified graphene quantum dots / ZnO gas sensitive material according to claim 1, characterized in that: In step S2, the ZnO seed crystals are loaded on the Al2O3 gas-sensitive ceramic tube by a drop coating method, and the drop coating-drying cycle is repeated 5 to 8 times, and the tube is placed in a 100°C oven for drying for standby use.
4. The in-situ preparation method of modified graphene quantum dots / ZnO gas sensitive material according to claim 1, characterized in that: The amount of citric acid used in step S3 is 0.5-1.5 g, and the heating and melting time at 180° C. is 2 h.
5. The in-situ preparation method of modified graphene quantum dots / ZnO gas sensitive material according to claim 1, characterized in that: The amount of the graphene quantum dot solution in step S4 is 1 to 4 mL.
6. The in-situ preparation method of modified graphene quantum dots / ZnO gas sensitive material according to claim 1, characterized in that: In step S4, the concentration of the zinc chloride aqueous solution is 1.50 mol / L, the concentration of the sodium carbonate aqueous solution is 0.80 mol / L, and the molar ratio of the sodium dodecyl sulfate to the zinc chloride is 1:65-70.
7. The in-situ preparation method of modified graphene quantum dots / ZnO gas sensitive material according to claim 1, characterized in that: In step S4, the temperature of the hydrothermal reaction is 110 to 170° C., and the time of the hydrothermal reaction is 12 to 24 hours.
8. The in-situ preparation method of modified graphene quantum dots / ZnO gas sensitive material according to claim 1, characterized in that: In step S5, the solvent thermal reaction temperature is 150-180° C., and the reaction time is 2-4 hours.
Citation Information
Patent Citations
Cr2O3 or NiO porous film material using WO3 as base material and method for manufacturing air-sensitive sensor
CN102248737A
Gas sensitive element with zinc oxide nanorod film as well as preparation method and application of gas sensitive element
CN113820364A
Production of thick film type gas sensitive element
JP1990082150A
Sensing material for high sensitivity and selectivity
WO2020172805A1
Cited By
In-situ construction method and application of gas sensor for detecting volatile aroma substances
CN120507408A